Diagnóstico do uso dos espaços na Universidade Estadual de Feira de Santana (UEFS): subsídios para elaboração do plano diretor para o campus - Silva, Maria do Socorro (2020)
The work aims to identify how much the existing buildings on the Campus of the State University of Feira de Santana (UEFS) meet the current and future needs of the collegiate sectors, in order to elaborate a diagnosis capable of providing information regarding the occupation of the built spaces, important element to be considered in the elaboration / update of the master plan. It was assumed that the current situation does not meet the demands that have been growing in recent years. In addition, there is also the issue of the distribution, management and signaling of campus spaces. In order to carry out this work, the methodological path used was exploratory research, with a qualitative and quantitative approach in which documentary researches were carried out in the institution's archives, interviews with professionals responsible for the construction and application of questionnaires, research by digital means, Google Forms, along with the defined sectors. The implementation of new buildings designed to meet the demands of the university community, currently, partially obeys defined criteria, which still follow the guidelines of the project called "Master Plan" developed in the 1970s, when the Campus was initially implanted. Although without the registration of this occupation and use of the land convention, it goes against the grain of several higher education institutions in the country that have already implemented or are in the process of implementing master plans for their campi. At UEFS, the physical expansion of the Campus took place gradually over the past four decades and the buildings were built as the demands of the courses for spaces and the availability of financial resources arose. It was found that the courses recently implemented are the ones that demand the most space, since they do not have their own buildings for their activities. The greatest demands are for classrooms and teachers, accessibility and mobility do not allow everyone access, and the existing signaling is not enough to guide users of spaces.